2021
DOI: 10.3389/fphar.2021.682654
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Culture of Ameloblast-Originated HAT-7 Cells for Functional Modeling of Defective Tooth Enamel Formation

Abstract: Background: Amelogenesis, the formation of dental enamel, is well understood at the histomorphological level but the underlying molecular mechanisms are poorly characterized. Ameloblasts secrete enamel matrix proteins and Ca2+, and also regulate extracellular pH as the formation of hydroxyapatite crystals generates large quantities of protons. Genetic or environmental impairment of transport and regulatory processes (e.g. dental fluorosis) leads to the development of enamel defects such as hypomineralization.A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 72 publications
1
4
0
Order By: Relevance
“…In our study, SEM images revealed that Alg-CMC bioink could provide a favorable environment for HAT-7 cells to retain their round-shaped round morphology and promote their attachment to the scaffolds and be guided towards mineralization and differentiation, which are essential for the enamel-like tissue formation. This is in agreement with a previous study reporting the round morphology of the HAT-7 cells when co-cultured with dental pulp stem cells in biphasic scaffolds composed of chitosan-collagen I hydrogels where their viability and proliferation were supported [4]. ALP expression, as a marker of ameloblast differentiation and mineralization, that was detected via ALP staining of bioprinted HAT-7 cells further confirmed the mineralization potential of Alg-CMC bioink.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, SEM images revealed that Alg-CMC bioink could provide a favorable environment for HAT-7 cells to retain their round-shaped round morphology and promote their attachment to the scaffolds and be guided towards mineralization and differentiation, which are essential for the enamel-like tissue formation. This is in agreement with a previous study reporting the round morphology of the HAT-7 cells when co-cultured with dental pulp stem cells in biphasic scaffolds composed of chitosan-collagen I hydrogels where their viability and proliferation were supported [4]. ALP expression, as a marker of ameloblast differentiation and mineralization, that was detected via ALP staining of bioprinted HAT-7 cells further confirmed the mineralization potential of Alg-CMC bioink.…”
Section: Discussionsupporting
confidence: 92%
“…Among other strategies, bio-fillings that can be produced by dental stem cells could offer an ideal solution to biologically regenerate/restore the affected enamel tissue [3]. HAT-7 is a dental epithelial cell line generated by rat dental stem cells that has been used to study ameloblast differentiation and enamel formation [4]. Such epithelial stem cells could be used as a base for new promising approaches that would employ the three main elements of tissue regeneration i.e.…”
Section: Introductionmentioning
confidence: 99%
“…HAT-7 cells derived from rat molars are functional ameloblast-like cells expressing amelogenin and ameloblastin proteins ( Kawano et al, 2002 ). They are often the cell line of choice for examining functional cell polarization ( Bori et al, 2016 ), the epithelial-mesenchymal interactions during odontogenesis ( Matsumoto et al, 2011 ), and for modeling disease ( Földes et al, 2021 ). When cultured on permeable transwell filters, HAT-7 cells formed polarized epithelial layers as characterized by apical membrane permeability to CO 2 and basolateral membrane uptake of bicarbonate ( Bori et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reliable in vitro 3D cell culture models have proven invaluable for examining the interactions between ameloblasts and the enamel extracellular matrix ( He et al, 2010 ; Földes et al, 2021 ). In vitro and cell culture systems provide for precise control over experimental conditions and the ability to isolate and examine the role of individual components in the matrix.…”
Section: Introductionmentioning
confidence: 99%
“…198 It has been illustrated that HAT-7 spheroids formed in Matrigel could maintain their morphology as well as pH modulation ability and expressed ameloblast markers. 247 Therefore, regeneration of the enamel tissue using scaffold-based strategies seems as a promising approach. 248 Scaffolds have been made from both synthetic and natural biomaterials in the forms of sponges, hydrogels, and meshes for regeneration of enamel or enamel-dental tissues complexes.…”
Section: Novel Trends and State Of The Art Approaches For Enamel Repa...mentioning
confidence: 99%